Nivel de conocimiento sobre pasta dental fluorada en padres y profesores de preescolares - Mattos-Vela, Manuel Antonio (2013)
ABSTRACT: The study aimed to determine the level of knowledge about fluoride toothpaste based on the fluoride source for parents and teachers from preschool children. A questionnaire was applied in a representative sample of parents and all teachers working at preschool educational state institutions in the Molina district, Lima, Perú. The level of knowledge was classified into three levels: low (0-2 points), medium (3-5 points) and high (6-7 points). We used frequency distribution tables for the univariate analisys, the chi square test and Fisher exact test for the bivariate analisys. The most frequent level of knowledge about fluoride toothpaste was medium level in both, parents (n = 68, 45%) and teachers (n = 52, 58.4%). The item: brushing teeth with fluoride toothpaste can cure the initial decay, obtained (had) the lowest number of correct response 50 (33.1%) and 19 (21.4%) parents and teachers respectively. It was found that the level of knowledge related to sources of information about fluoride is in the case of parents, educational talk (p = 0.014) and the dentist (p = 0.003) were associated, whereas in the case of teachers, only statistically significant association was found with the educational talk (p = 0.013). The higher level of knowledge about fluoride toothpaste on parents and teachers was the middle level and was associated with the dentist and educational talk as major sources of information.